1992
DOI: 10.1111/j.1539-6924.1992.tb00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Markers of Environmental and Ecological Contamination: An Overview

Abstract: An approach, using biomarkers (biological responses) for assessing the biological and ecological significance of contaminants present in the environment is described. Living organisms integrate exposure to contaminants in their environment and respond in some measurable and predictable way. Responses are observed at several levels of biological organization from the biomolecular level, where pollutants can cause damage to critical cellular macromolecules and elicit defensive strategies such as detoxication and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 8 publications
(1 reference statement)
2
37
0
2
Order By: Relevance
“…Epidemiological data from consumption of unsafe water showed increased risk of nephrotoxicity, cancer and central nervous system defects [30,31]. Exposure to chemicals through drinking contaminated water is capable of inducing DNA damage and enhancing genetic changes in somatic cells that can result in decreased cell survival or transformation and eventual reproductive abnormalities and cancer formation in organisms [32,33]. The results of our study showed that the tested well water samples were contaminated by harmful substances.…”
Section: Discussionmentioning
confidence: 64%
“…Epidemiological data from consumption of unsafe water showed increased risk of nephrotoxicity, cancer and central nervous system defects [30,31]. Exposure to chemicals through drinking contaminated water is capable of inducing DNA damage and enhancing genetic changes in somatic cells that can result in decreased cell survival or transformation and eventual reproductive abnormalities and cancer formation in organisms [32,33]. The results of our study showed that the tested well water samples were contaminated by harmful substances.…”
Section: Discussionmentioning
confidence: 64%
“…Structural changes to the integrity of DNA caused by DNA-damaging agents are useful end points for assessing exposure to hazardous environmental pollutants on human health (2,3) and biota (4,5). The organism functions as an integrator of exposure, accounting for abiotic and physiologic factors that modulate the dose of toxicant taken up, and the resulting magnitude of the change in DNA structure provides an estimate of the severity of exposure, hopefully in time to take preventive or remedial measures.…”
Section: Introductionmentioning
confidence: 99%
“…A recent trend in the development of ecosystem impact criteria is the use of bioindicators and bioaccumulators to monitor and assess ecosystem changes as an alternative to the laborious construction and estimation of the various composite indexes (Shugart andothers 1992, Nimis 1990). …”
Section: Characteristics Of Impacts On Environmental Media and Receptorsmentioning
confidence: 99%